Breeding of yeast used in fruit juice fermentation through ARTP mutagenesis combined with ultraviolet mutagenesis - LIN Yonghong, LIU Shuai, JIANG Ting, ZHANG Na, ZHANG Shizhong, QIN Weishuai (Zhongguo niangzao, 2025)
In this study, using the yeast strain G4 without ethanol production but with high ester production as research object, the strain was identified by morphological observation and molecular biology techniques. With the strain G4 as the starting strain, a superior strain with low ethanol and high ester production was selected by atmospheric pressure and room temperature plasma (ARTP) mutagenesis combined with ultraviolet mutagenesis, and its genetic stability, tolerance and hemolysis safety were studied. The results showed that the strain G4 was identified as Rhodotorula glutinosa, and a superior mutant strain AU73 without ethanol production but with high ester production was obtained by mutation breeding, the total ester production was 1.10 g/L, which was 1.53 times that of the starting strain G4. The mutant strain AU73 had good genetic stability, tolerance and security, which could tolerate pH 2.5, ethanol volume fraction 10%, SO2 150 mg/L, and glucose 30%. In summary, the mutant strain AU73 had the characteristics of no ethanol production and high ester production, which provided a theoretical basis for improving the quality of fermented fruit juice and reducing the production cost.